Formulation And Evaluation Of Palm Oil Esters Based Nanoemulsion For Topical Delivery Of Ketoprofen - Sakeena, Mohamed Hameem Fatima (2010)

(untitled)
In this study emulsions with varying ratios of surfactant or its mixtures (Tween 80®, Tween 85® and Span 20®) were prepared using POE as the oil phase. The transparency of the mixtures was used as visual indications that nano-emulsions were formed and were reconfirmed by measuring the droplets size using laser scattering spectroscopy (Nanophox). The gel area of the triangle phase diagrams produced was used as one of criteria to determine the suitable HLB value of the nano-emulsion’s emulsifier for POE and for selection of several promising formulae. It was noted that largest gel area produced by HLB 15, 13.72 and 12. From these three phase diagrams three common points namely A, B and C were selected and mixtures of POE and surfactant constituted in them were used to study the solubility of ketoprofen.